O impacto do programa bolsa família sobre a repetência: Resultados a partir do cadastro único, projeto frequência e censo escolar - Luis Felipe Batista de Oliveira; Sergei S. D. Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This text attempts to estimate the impacts of Bolsa Família upon grade repetition using matched data from the Single Registry, the Attendance Project and the annual school censuses. Three approaches are used: i) comparison of results for poor children in the Single Registry with and without the benefit; ii) estimation of treatment effect; and iii) estimation of the impact of the percentage of beneficiary children in a given school upon the average repetition in the school. The results are far from impressive but do show a modest drop in the probability of grade repetition.
Keywords: I24; I28; I38; 330; education and inequality; government policy; conditional cash transfers